Effectiveness Test of a 96% Ethanolic Extract Cream of Sambung Nyawa Leaves (Gynura procumbens L.) on Incision Wounds in Male White Rats - Chandra Pranata; Hasni Yaturramadhan Harahap; Herlina Herlina; Anissa Jelita Silitonga (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: A major challenge in wound care is the high risk of infection and the relatively prolonged healing process. Synthetic antiseptics such as povidone iodine remain widely used as first-line therapy; however, prolonged use has been reported to cause adverse effects, including tissue irritation and the potential to delay epithelialization under certain conditions. Therefore, alternative therapies that are safer, more effective, and accessible to the community are needed. One promising approach involves the use of traditional medicinal plants known to possess antiseptic, anti-inflammatory, astringent, and antibacterial properties. Sambung Nyawa leaves (Gynura procumbens L.) have been empirically used in Indonesia to treat various health conditions, including skin wounds. This study aimed to evaluate the wound healing effect of an ethanol extract cream of Sambung Nyawa leaves and to determine the most effective concentration for incision wound healing. Methods: A true experimental method with a post-test only control group design was employed. The study subjects were male white rats (Rattus norvegicus) with standardized incision wounds. The animals were treated with Sambung Nyawa leaf extract cream at concentrations of 5%, 10%, and 20%, along with a positive control group (povidone iodine) and a negative control group. The observed parameter was wound diameter following treatment. Results: The findings indicated that the 20% cream concentration demonstrated the fastest healing time, followed by the 10% and 5% concentrations, the positive control, and the negative control. Differences in wound diameter among treatment groups suggest that Sambung Nyawa leaf extract has the potential to accelerate the wound healing process. Conclusion: Cream formulations containing 5%, 10%, and 20% extract exhibited effectiveness relatively comparable to povidone iodine, indicating their potential for development as a natural alternative therapy for incision wounds.